UPAYA PEMBIASAAN PENDIDIKAN KARAKTER ISLAMI PADA ANAK KELOMPOK B1 DI KB/BA RESTU 1 MALANG - Khadija Arif; Rosichin Mansur; Mutiara Sari Dewi (Jurnal Dewantara, 2021)
Based on the result of preliminary observation on Saturday, October 5 2019 at KB / BA Restu 1 Malang, the character of group B1 showed disrespectful behavior. So, in this case the researcher intended to carry out research, namely about the planning of the habituation of Islamic character education in children group B1 in KB / BA Restu 1 Malang, the implementation of the habituation of Islamic character education in children group B1 in KB / BA Restu 1 Malang and supporting and inhibiting factors in implementation the habituation of Islamic character education in B1 group children in KB / BA Restu 1 Malang. In this study, researcher used a qualitative approach and type of case study research. Researcher collected data using observation, interview and document techniques. The result obtained from the results of observation, interview and document can be concluded that the effort to get the habit of Islamic character education in children group B1 in KB / BA Restu 1 Malang has been very good, it can be seen from the design and implementation carried out in school.